Effectiveness of Communication Channels in The Implementation of The Butimba Water Development Project, Mwanza City, Tanzania - John Matoke Mkama,; Camillus Nikata,; Leah Mwainyekule, (Technium Social Sciences Journal, 2025)
Purpose: This study evaluates the effectiveness of communication channels used during the implementation of the Butimba Water Development Project in Mwanza City, Tanzania. It aims to (a) identify which channels were employed, (b) assess their capacity to promote stakeholder participation and feedback, and (c) determine how audience-centred message design influenced comprehension, trust, and perceived influence. Methodology: A sequential explanatory mixed-methods design was used. Quantitative data were collected via a household survey (N = 100) that measured exposure to and perceived credibility of channels, awareness, meeting attendance, and perceived influence. Qualitative data were gathered through eight key-informant interviews with implementing agency staff and community leaders to explain observed patterns and institutional practices. Descriptive statistics and χ² tests analysed survey data; thematic analysis was applied to interview transcripts. Findings: The project deployed a multi-channel strategy dominated by stakeholder meetings, social media/WhatsApp groups, public-address systems, posters/billboards, radio broadcasts, and mobile notifications (SMS/IVR). While overall awareness of the project was high, communication remained largely unidirectional: institutional feedback mechanisms were weak or underused, only a minority of residents perceived their views as considered in decisions, and participation tended to be passive rather than deliberative. Age and education shaped channel preferences (younger residents favoured digital channels; older residents relied on radio and meetings). Unique contribution to theory, policy, and practice: The study contributes to theory by empirically demonstrating a common “two-way asymmetry” in urban water projects where multi-channel reach does not equate to symmetrical dialogue and by proposing an integrated PR + Social Marketing framing for evaluating channel effectiveness. For policy, it offers concrete, budget-sensitive prescriptions (e.g., SMS/IVR shortcodes, documented feedback protocols, and communication KPIs) that can be embedded into project appraisal and funding conditions. For practice, it provides a tested hybrid communication framework that pairs trusted traditional media with targeted digital feedback tools and institutionalised response processes to increase perceived influence, trust, and sustainability.